Análise do perfil clínico-epidemiológico de pacientes atendidos no centro de referência de imunobiológicos especiais da Fundação Santa Casa de Misericórdia do Pará. - QUARESMA, Emanuelle Negrão (2023)
The Immunologic Reference Center-CRIE of Santa Casa Hospital-FSCMPa, part of Health Ministery, supply vaccines with high immunologic quality for deprived people. All the 43 CRIES works in a team composed by a doctor, a narse and a technical, qualifieds in the immunologic area. This center availables the inactive vaccine to poliomielite (VIP), vaccine to A hepatite, varicele, Influenza, anti pneumococo, triply acelular (DTPa) and to meningococo. The immunoglobulines are the human anti B hepatite, the antizoster varicella and anti-rabies. This retrospective transversal, descriptive and analytic study value the clinic-epidemiologic profile of pacien that were served and vaccineted in this center in his first year of medical attention. Were reviewed 1.198 charts, 236 excluseds, being 962 the final sample. Women were more prevalent (58,9%), being one mouth up to one year old the average age (35%). About 66% of the cases were from of Belém city and the mayorty just come from the FSCMPa. The main send cause were prematurity (30,6%) with healthy diagnosis (36%), being 20.9% health professional group. Within the pacients the FSMPa premature clinic were the responsible for the mayority of the outpacients. The vaccine more applied were pneumococcal 7 valente (802 doses), followed by influenza (790 doses). The antizoster varicelle were the immunoglobuline more used (5 doses) and the Anti B hepatite the second (4 doses). This can show the need more stimulus from others speciality area respect to the correct moment to send the pacients for an special Immunologic Center and and take advantage in each consultation.